Description of the tadpole of Hylarana darlingi Boulenger 1902 (Anura: Ranidae) from the Mulanje Area, Malawi - Conradie, Werner; Tweddle, Denis; Mäkinen, Tuuli; Bills, Roger (Zootaxa, 2012)
The generic placement of the African Hylarana is still under debate (Frost 2011). We follow the latest taxonomy (Frost 2011) and refer to the genus as Hylarana. Of the eleven African species, only H. darlingi and H. galamensis have been recorded from Malawi (Mercurio 2011). We report the second confirmed record of H. darlingi in Malawi. Tadpoles of African Hylarana species are poorly known: descriptions are available for H. lemairei (Schmidt & Inger 1959; Channing 2001), H. albolabris (Channing & Howell 2006) and H. galamensis (Rödel 2000; Channing & Howell 2006; Du Preez & Carruthers 2009).